The Representation of Sexual Violence Against Women in The Film Cairo 678: a Roland Barthes Semiotic Analysis - Nurfadilah Nurfadilah; Rohanda Rohanda (Gunung Djati Conference Series, 2025)
This study examines the representation of sexual violence against women in the Egyptian social drama Cairo 678 (2010), employing Roland Barthes' semiotic approach. The film was chosen for its bold exploration of the critical issue of sexual violence in Cairo’s public spaces and women’s resistance against it. Using Barthes’ framework of denotation, connotation, and myth, this research aims to reveal how the film’s visual and narrative signs depict sexual violence while dismantling patriarchal myths that normalize such acts. The study adopts a descriptive qualitative method, with data consisting of scenes, dialogues, and audiovisual elements from Cairo 678. Data collection techniques include documentation-based observation and literature review. Barthes’ semiotic analysis is applied through stages of sign identification, denotation (literal meaning), connotation (cultural and emotional meaning), and myth (naturalized ideology). The findings demonstrate that Cairo 678 explicitly portrays various forms of sexual violence against women, ranging from non-verbal harassment and physical assault to severe collective sexual violence. This representation operates not only at the denotative level but also constructs powerful connotations of victim helplessness, anger, and trauma, while critiquing the failures of social and legal systems.